2014
DOI: 10.2478/raon-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated chemotherapy and erlotinib for advanced NSCLC: high proportion of complete remissions and prolonged progression-free survival among patients with EGFR activating mutations

Abstract: BackgroundPharmaco-dynamic separation of cytotoxic and targeted drugs might avoid their mutual antagonistic effect in the treatment of advanced non-small cell lung cancer (NSCLC).Patients and methods.Eligible patients were treatment-naive with stage IIIB or IV NSCLC. In addition, inclusion was limited to never-smokers or light smokers or, after 2010, to patients with activating epidermal growth-factor receptor (EGFR) mutations. Treatment started with 3-weekly cycles of gemcitabine and cisplatin on days 1, 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…In vitro studies showed that pretreatment with erlotinib caused arrest of cells in G1 phase, decreasing the cytotoxicity of chemotherapy and reducing apoptosis, which would negatively affect the efficacy of chemotherapy [17]. One the other hand, it was discovered that temporary discontinuance of TKIs before chemotherapy allows the cancer cells to re-enter the cell cycle, restoring their sensitivity to chemotherapy [18][19][20]. The strategy was also supported by FASTACT-2 and several other clinical researches [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that pretreatment with erlotinib caused arrest of cells in G1 phase, decreasing the cytotoxicity of chemotherapy and reducing apoptosis, which would negatively affect the efficacy of chemotherapy [17]. One the other hand, it was discovered that temporary discontinuance of TKIs before chemotherapy allows the cancer cells to re-enter the cell cycle, restoring their sensitivity to chemotherapy [18][19][20]. The strategy was also supported by FASTACT-2 and several other clinical researches [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“… 28 Sporadically a NMR was done to evaluate the operability of some patients 29 and a PET-CT was also done in some patients to evaluate the extent of disease and response to treatment like in patients with lung cancer. 30 …”
Section: Methodsmentioning
confidence: 99%
“…Neutropenia is a major risk factor for the development of infection in cancer patients undergoing treatment with chemotherapy. 2,3 Fever remains the most prevalent and evident sign of infection in neutropenic cancer patients and early initiation of broad-spectrum antibiotic therapy significantly reduces mortality in these patients. 47 …”
Section: Introductionmentioning
confidence: 99%